Molecular characteristics of the gyrA gene among rifampicin-resistant Mycobacterium tuberculosis isolates - Aquaresta, Febriana; Kuntaman, Kuntaman; Dewi, Lisa; Syaiful, Irbasmantini (Journal of Clinical Microbiology and Infectious Diseases, 2025)
Background: Drug-resistant tuberculosis (TB) remains a public health threat, especially during this pandemic. Meanwhile, fluoroquinolone is used as a second-line multidrug-resistant TB (MDR-TB) treatment since this drug was previously prescribed for respiratory, urinary, and genital tract infections. However, unregulated and excessive use of fluoroquinolones leads to resistance. Methods: The design of this study is a descriptive observational study with a cross sectional approach. This study aims to determine the pattern of gyrA gene mutation in fluoroquinolone resistance among rifampicin-resistant Mycobacterium tuberculosis isolates during the COVID-19 pandemic in Sumatra, Indonesia. The Mycobacterium tuberculosis isolates were stored in the Palembang Health Center Laboratory as the referral laboratory in Sumatra from January to December 2020. Out of the 233 isolates that were tested phenotypically by BACTEC MGIT, 8 isolates of fluoroquinolone resistance (ofloxacin or moxifloxacin or both) were obtained and sequenced using an ABI PRISM 3730XL analyzer for Single Nucleotide Polymorphism analysis (SNP). Results: Among the six fluoroquinolone-resistant Mycobacterium tuberculosis isolates, the gyrA mutations were identified in 5/6 isolates (84%), A90V (34%), D94A (16%), and D94G (34%), while 1/6 isolates (16%) had no mutation in gyrA gene among Mycobacterium tuberculosis that were fluoroquinolone resistance. Conclusion: The gyrA gene mutation in fluoroquinolone resistance among rifampicin-resistant Mycobacterium tuberculosis was commonly present in codon 90 (2/6 isolates =32%) and 94 (3/6 isolates=68%).